Formation of the Conscience: Pedagogic Acting or Bargaining? - Leo Vam Der Tiun (Jesuit University Ignatianum in Krakow, 2017)
After a short historical draft of the pillarized Dutch society and the praxis of the formation of conscience in the time of "Rich Roman Catholic Life", a picture is made of the once tolerant and in the meantime extremely secularized Netherlands, which is often called a leading country in political and ethical issues and an experimental garden of religiosity. Next the focus is on evil in our time. The conception of sin and awareness of guilt have changed in the previous decades under the influence of secularization and individualization. The question is now aggravated to the experience of evil and the formation of conscience in the subculture of youth. A glance is taken at their world of the Internet and TV, of chatting on the Net and video clips on the music channels MTV and TMF. There is the question of the relation between violence and sex in the media and youth's behaviour. Finally, this leads to the question as to what the formation of conscience means nowadays. The formation of conscience is an important aspect of upbringing. And this can be done in various ways: in the way of passing on cultural achievements, in the way of allowing what is present in the educandus to develop, in theway of the communicative exchange of ideas and in the way ofactive presence close to the educandus, which seems to be the most proper way in this modern world and time.